Elaboração de projeto de fundação em sapatas isoladas com carga centrada para barracão em Campo Grande/MS - Marques, Pedro de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
Neste trabalho foi elaborada uma solução para as fundações estruturais de um galpão hipotético, localizado na cidade de Campo Grande, Mato Grosso do Sul. Para execução do projeto foi definido que o tipo de fundação a ser executada. Optou-se pelo uso de sapatas com carga centrada. Assim, foi analisado o laudo SPT bem como as dimensões das sapatas frente as cargas dos pilares. O método de sapatas isoladas com carga centrada pode ser escolhido devido a não observância de nível d’agua no perfil SPT obtido do terreno a ser executada a obra e o atendimento as normas brasileiras – NBR.

In this work, a solution was developed for the structural foundations of a hypothetical warehouse located in Campo Grande, Mato Grosso do Sul, Brazil. For the project execution, the type of foundation to be implemented was defined. The choice was made for the use of footings with centered load. Thus, an analysis of the SPT report was carried out, as well as the dimensions of the footings in relation to the loads of the pillars. The method of isolated footings with centered load was chosen due to the absence of a water table in the SPT profile obtained from the site where the construction will take place, in addition to compliance with Brazilian standards – NBR
Design of isolated footings with centered load for a shed in Campo Grande/MS
Keywords: Laudo SPT; Fundações estruturais; Sapata com carga centrada; SPT report; Structural foundationsstructural foundations; Footing with centrally applied load